Nutritional guidelines and energy needs for the female athlete: preventing low energy availability and functional amenorrhea through diet - Robert-McComb, J. J.; González, Á. G. (The Active Female, 2014)
The prevalence of secondary amenorrhea, in athletes, varies widely with sport, age, training volume, and body weight. Studies over different athlete populations report rates of menstrual disorders ranging from 1 to 69 % and of 70 % for subclinical ovarian disturbances in athletes, while, on the other side, only about 2-15 % of sedentary youth women have menstrual irregularities. Studies showed that normal menstrual cycling is altered if there is a restriction in energy availability, that is, the amount of dietary energy remaining for other body functions after exercise training. When energy availability is too low, physiological mechanisms reduce the amount of energy used for cellular maintenance, thermoregulation, growth, and reproduction. This compensation tends to restore energy balance and promote survival but impairs general health. Studies consistently show that female athletes are not consuming enough energy to support their activity levels, and low energy and nutrient intake places these athletes at a greater risk for nutrition-related disorders such as amenorrhea, osteoporosis, iron-deficiency anemia, and eating disorders. This is not just a problem for those athletes that practice sports with a thigh weight control but for all women practicing high-level sports. So, individual nutritional assessment and dietetic advice are pillars for maintaining health and good performance. Nutritional educational projects must be carefully designed by a multi-professional team and should involve not only the sportive women but also coaches and family to be successful in facilitating athletes the right skills for adopting healthy eating habits. A joint position statement by the American College of Sports Medicine, the American Dietetic Association, and the Dietitians of Canada states that a diet substantially different from that recommended in the Dietary Guidelines for Americans is not needed for athletes, once enough calories are ingested to meet their energy needs. It is recommended that an athlete`s diet should consist of nutrient-dense food and beverages within and among the basic good groups while choosing foods that limit the intake of saturated and trans fats, cholesterol, added sugars, salt, and alcohol.